Changes of Corneal Thickness and Intraocular Pressure in Type II Diabetic Patients - Yasmena Abdulhadi; Suliman Masuod; Wafa Lareibi; Mohamed Eldursi (Khalij-Libya Journal of Dental and Medical Research, 2021)
Aims. The purpose of the present paper is to present the results of central corneal thickness & intraocular pressure measurements in diabetic patients with or without retinopathy, and compare the results with non-diabetic control patients. Methods. Total number was 152 patients were 152 eyes The study group was divided into 3 groups as following: 50 non diabetic (control). 50 diabetic type II with no diabetic retinopathy. 52 diabetic type II patient with diabetic retinopathy. Correlation analysis was performed to assess the association between glycosylated hemoglobin levels& Intraocular pressures and retinal changes among subgroups. Results. Demographic characteristics of study and control groups were similar (P>0.05). Mean CCT 553.62 with Std deviation (14.47) in control cases and 622.27 with Std deviation (507.09) in diabetic cases which is more than control however the distinction failed to reach applied math significance were (p value= > 0.05). additionally, CCT and diabetic retinopathy association was significant were CCT in diabetic patients with no retinal changes was 563.96 Std deviation (18.85) and in diabetic patients with retinopathy was 670.45 Std deviation (717.2) and P value = 0.004 (significant). There was significant correlation between increased corneal thickness and intraocular pressure were p-value = 0.002. Conclusions. We found that the central cornea of diabetic patients is thicker when compared with non-diabetic patients. Thicker central cornea associated with diabetes mellitus should be taken into consideration while obtaining accurate intraocular pressure measurements in diabetics.